Experimental evaluation of BBR congestion control - Hock, Mario; Bless, Roland; Zitterbart, Martina (2017 IEEE 25th International Conference on Network Protocols (ICNP), 2017)
BBR is a recently proposed congestion control. Instead of using packet loss as congestion signal, like many currently used congestion controls, it uses an estimate of the available bottleneck link bandwidth to determine its sending rate. BBR tries to provide high link utilization while avoiding to create queues in bottleneck buffers. The original publication of BBR shows that it can deliver superior performance compared to Cubic TCP in some environments. This paper provides an independent and extensive experimental evaluation of BBR at higher speeds. The experimental setup uses BBR's Linux kernel 4.9 implementation and typical data rates of 10Gbit/s and 1 Gbit/s at the bottleneck link. The experiments vary the flows' round-trip times, the number of flows, and buffer sizes at the bottleneck. The evaluation considers throughput, queuing delay, packet loss, and fairness. On the one hand, the intended behavior of BBR could be observed with our experiments. On the other hand, some severe inherent issues such as increased queuing delays, unfairness, and massive packet loss were also detected. The paper provides an in-depth discussion of BBR's behavior in different experiment setups.